Some Results in the Numerical Analysis of Structural Instabilities Part I. Statics - Kleiber, M. (Engineering Transactions, 1982)
Some problems of nonlinear structural statics are dealt with in the paper. Attention is restricted to numerical analyses carried out by means of the finite element method. The paper contains a short discussion of the static stability problem which is followed by a number of numerical examples.